Board commissioner characteristics and intellectual capital on company financial performance in banking industries - Lia Uzliawati (Postgraduate Program Merdeka University, 2025)
This research aims to examine the influence of board commissioners characteristics on the company's financial performance and test whether intellectual capital can moderate the relationship between the characteristics of the board of commissioners and company performance. The characteristics of the board of com-missioners in this study are proxied by the size of the board of commissioners and independent commissioners. The sample used in this research is banking companies listed on the Indonesian Stock Exchange for the 2020-2023 period with a total of 123 observations. The size of the board of commissioners is measured using the total number of board of commissioners in the Company, while independent com-missioners are measured by the percentage of independent commissioners and the number of board of commissioners in the Company. The company's financial performance is measured using return on assets and intellectual capital is measured using VAICTM. Moderating Regression Analysis (MRA) is used as an analytical tool in this research. The research results show that the size of the board of commissioners does not have a significant influence on the company's financial performance. Meanwhile, independent commissioners have a significant positive influence on the company's financial performance. Furthermore, intellectual capital can moderate the relationship between the characteristics of the board of commissioners and company performance. JEL Classification: G32, O34 DOI: https://doi.org/10.26905/afr.v7i3. 13284